2020
DOI: 10.18488/journal.73.2020.84.450.463
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Entrepreneurial Self-Efficacy and Innovation on Firm Performance: Evidence from Thai Startup Firms

Abstract: This study is one of very few studies which have investigated all aspects of firm performance using balanced scorecard (BSC) of Thai startup firms through the exploration of entrepreneurial selfefficacy and types of innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
3
6
0
1
Order By: Relevance
“…Overall, the results confirm the general wisdom in entrepreneurship that cognitions can increase innovation within the firms. Such a consistent understanding can be seen in the results reported by different researchers (e.g., Ashourizadeh et al, 2014;Newman et al, 2018;Thavorn et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Overall, the results confirm the general wisdom in entrepreneurship that cognitions can increase innovation within the firms. Such a consistent understanding can be seen in the results reported by different researchers (e.g., Ashourizadeh et al, 2014;Newman et al, 2018;Thavorn et al, 2020).…”
Section: Discussionsupporting
confidence: 82%
“…Such a consistent understanding can be seen in the results reported by different researchers (e.g. Ashourizadeh et al ., 2014; Newman et al ., 2018; Thavorn et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As a conclusion, it can be seen that there is a statistically significant effect at the 0.05 level of significance for the Entrepreneurial Self-Efficacy on the performance of the small business in skikda (this result synchronizes with the results of Srimulyani, Hermanto, 2022;Zubair et al, 2021;Shen et al, 2021;Klongthong et al 2020), whereas (27.7%) of changes in the performance of the small business in Skikda resulting from the change in the level of the Entrepreneurial Self-Efficacy, Which calls for the need to work to enhance this efficiency for the owners of these businesses, especially in light of competition and the increase in the number of this type of business in Algeria.…”
Section: Discussionsupporting
confidence: 71%
“…Several studies at the institutional level and in the field of entrepreneurial behavior have shown a positive effect of the entrepreneurial self-efficacy component as one of the internal entrepreneurial capabilities on the performance and competitiveness of small and medium enterprises (Srimulyani, Hermanto, 2022;Zubair et al, 2021;Shen et al, 2021;and Klongthong et al, 2020), This is what the research seeks through the essential question of the impact that entrepreneurial self-efficacy can have on the performance of small enterprises in Algeria (Skikda).…”
Section: A Messikhmentioning
confidence: 99%
“…The advantages of using behavioral loyalty as a measurement construct include that 1) it is based on actual purchases, which are directly related to a firm's performance and existence (Klongthong et al, 2020), it is likely to be incidental, i.e., based on behavior over a period of time; and 3) it is relatively easier to collect than attitudinal data. However, the construct is limited in that it is difficult to distinguish between brand loyalty and repeat buying, which can obscure spurious loyalty.…”
Section: Brand Loyaltymentioning
confidence: 99%